2021
DOI: 10.30918/aerj.92.21.087
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the CEFR in Turkish national curriculum

Abstract: Despite the ongoing attempts in Turkey to teach the English language to Turkish citizens so that they can communicate effectively in global contexts, the results reached are much lower than desired. To determine where the mistakes originate, different policies have been followed, course hours and instructional strategies have undergone constant changes. The curriculum which is one of the most important pillars of teaching and learning has been updated according to the principles of the CEFR which deeply affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Even though this circumstance creates challenges for translators, it also has positive cross-cultural impact in that it informs and updates target audience about recent developments and innovations in language education field (Günday & Aycan, 2018). Considering the results of the research, it could be stated that the study is noteworthy in that it offers a distinctive perspective on cross-cultural impact of CEFR within Turkish context from the perspective of translation studies even though there are several studies on CEFR related to paradigm shift it caused in foreign language education (Byram & Parmenter, 2012;Çelik, 2013;Hazar, 2021;Sahib & Stapa, 2021).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Even though this circumstance creates challenges for translators, it also has positive cross-cultural impact in that it informs and updates target audience about recent developments and innovations in language education field (Günday & Aycan, 2018). Considering the results of the research, it could be stated that the study is noteworthy in that it offers a distinctive perspective on cross-cultural impact of CEFR within Turkish context from the perspective of translation studies even though there are several studies on CEFR related to paradigm shift it caused in foreign language education (Byram & Parmenter, 2012;Çelik, 2013;Hazar, 2021;Sahib & Stapa, 2021).…”
Section: Resultsmentioning
confidence: 88%
“…CEFR is a framework describing language proficiency levels and providing instruction for learning, teaching and testing languages (Cefr, 2001;Hazar, 2021). Given that the subject matter of CEFR analyzed deeply, it is observed that the document includes content with rich terminology and concepts related to foreign language education.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Some procedural aspects that are embodied in the curriculum proper such as the use of tasks, promotion of learning strategies and teaching of key competences and values are far from being transparent and some others appears to be misunderstood as seen in the methodology of the curriculum. Concerning this, Hazar (2021) suggests that a more thorough understanding of the CEFR is needed if English teaching in Turkey is to benefit from its offerings to the full. For this reason, it might be reasonable to elucidate or review some of the methodological and procedural aspects so the process dimension of the curriculum can be strengthened.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Oral production is a speaking activity. The language user produces an oral text which is received by an audience of one or more listeners (Hazar, 2021). The scales are provided for sustained monologue: describing an experience, sustained monologue: giving information, sustained monologue: putting a case, public announcements, and addressing audiences.…”
Section: Production Activitiesmentioning
confidence: 99%